Klaus R. Kunzmann als Initiator und Impulsgeber bei der Entwicklung von Städten und von Regionen in Deutschland durch Kultur- und Kreativwirtschaft. - Ebert, Ralf (Routledge, 2017)
Dieser Aufsatz konzentriert sich auf die zahlreichen Studien und Projekte, die Klaus R. Kunzmann am Institut für Raumplanung der Universität Dortmund mit seinem Team und seither mit dem Autor bzw. mit STADTart zur Kultur- und Kreativwirtschaft durchgeführt hat. Darüber hinaus hat er noch zahlreiche andere Städte und Regionen in Deutschland in diesem Handlungsfeld beraten und tut dies auch weiterhin. Dies gilt ebenso hinsichtlich der Publikation von Aufsätzen. Deshalb gibt die Darstellung nur einen kleinen Ausschnitt seines Schaffens in diesem Handlungsfeld wieder.

Within the continuing hype surrounding cultural and creative industries something has unfortunately been forgotten: for several decades now, Klaus Kunzmann has been one of the key figures in the dissemination of this interdisciplinary sector in terms of action and policy fields of cities and regions in Germany, in particular in the Ruhr region. At the end of the 1980s, "cultural industry", as it was referred to, initially dealt with the sector's impact on the economy and employment. Since then the focus has been on the link between the publicly subsidised cultural sector and the cultural and creative industries, as well as the spatial dimensions of the branch in terms of urban development ("creative spaces"). Within these thematic and policy areas, Kunzmann has for many years been developing action plans and strategies, and this paired with a dose of criticism from the point of view of a planning practitioner and everyday knowledge about political decision-making processes, along with, in many cases, ostensibly utopian ideas. His exploratory, practical and rather "design-oriented planning theory" as regards the willingness of actors in politics and management in cities and regions to take action was - and still is - in many cases ahead of its time. This probably also applies to his current scepticism with regard to the further development of cultural and creative industries.
Keywords: Raumplanung; Planungstheorie; Stadtentwicklungsplanung; Raumforschung; Wirtschaftsförderung; Kultur; Standort; Kulturwirtschaft; Kreativwirtschaft; Handlungsfeld; Kreatives Milieu; Standortentwicklung